Petrology and geochemistry of Li-bearing pegmatites and related granitic rocks in southern Thailand: implications for petrogenesis and lithium potential in Thailand - Fanka, Alongkot; Tadthai, Jaruphichaya (Frontiers in Earth Science, 2023)
Lithium (Li) can be found in many minerals, including lepidolite. Lepidolite is found in pegmatite-related tin deposits in the Phang Nga area in southern Thailand. According to their field occurrence, petrography, mineral chemistry, and whole-rock geochemistry, the Li-bearing pegmatites and the granitic rocks in the study area can be linked to tin deposits in southern Thailand as part of the SE Asian tin belt. The Li-bearing pegmatites are characterized by an abundance of lepidolite, K-feldspar, plagioclase, and quartz with some accessory minerals of fluorite, cassiterite, apatite, monazite, and beryl. The granitic rocks show various compositions, including porphyritic biotite–muscovite granite, biotite granite, and muscovite–tourmaline granite with different proportions of K-feldspar, plagioclase, quartz, biotite, muscovite, and tourmaline. Whole-rock geochemistry indicates that both the Li-bearing pegmatites and granitic rocks have a close relationship rooted in their peraluminous S-type granite affinity. The Li-bearing pegmatites evolved from highly fractionated S-type granitic rocks comparable with the Western Belt Granite of Thailand. The enrichment of large-ion lithophile elements (e.g., Rb and K) and the depletion of Ba, Nb, and Ti together with similar rare earth element patterns reflect the collisional setting indicating the Sibumasu–West Burma and West Burma–Indo-Burma collisions during the Cretaceous to the Eocene. The crystallization pressure–temperature conditions of these rocks were 3.49–4.25 kbar and 622°C–675°C, respectively, with an emplacement depth of 13–15 km. The Li-bearing pegmatites had a relatively high average Li grade compared with those of other Li-bearing pegmatites in the world.